Player-surface interactions: perception in elite soccer and rugby players on artificial and natural turf - Strutzenberger, G.; Edmunds, R.; Nokes, L. D. M.; Mitchell, I. D.; Mellalieu, S. D.; Irwin, G. (Sports Biomechanics, 2022)
Artificial turf (AT) is common at all levels of soccer and rugby. Employing an interdisciplinary design, this study aimed to examine the extent to which the negative attitude commonly expressed by players concerning AT is based on the difference in technique between AT and natural turf (NT), or due to pre-existing biases. Thirty professional soccer and rugby players performed a defined set of movements with masked and normal perception conditions on NT and AT. Two-dimensional kinematic analysis (100 Hz) of characteristics in parallel to a psychological assessment of the impact of cognitive bias for a playing surface was assessed. No significant interaction effects between the level of perception and surface type were found. For AT, contact time (CT) was shorter across conditions, while for NT rugby players had longer CT during acceleration/deceleration phases and shorter flight times. Pre-existing negative bias against AT was found during the normal perception trials in the technology acceptance model (Usefulness and Ease of Use) and the general preference questions on how much the athlete would like to play a game on it. The results suggest that opinion was not driven by surface characteristics, but by a cognitive bias, players brought with them to the pitch.